Privately Protected Areas: Missing Pieces of the Global Conservation Puzzle - Bingham, Heather C.; Fitzsimons, James A.; Mitchell, Brent A.; Redford, Kent H.; Stolton, Sue (Frontiers in Conservation Science, 2021)
Protected areas are an essential component of global conservation efforts. Although extensive information is available on the location of protected areas governed by governments, data on privately protected areas remain elusive at the global level. These are areas governed by private individuals and groups – ranging from families to religious institutions to companies – that meet IUCN’s definition of a protected area: a clearly defined geographical space, recognised, dedicated and managed, through legal or other effective means, to achieve the long-term conservation of nature with associated ecosystem services and cultural values. As the world’s governments prepare to adopt a new post-2020 global biodiversity framework to guide conservation over the next decade, we argue that, without complete data on privately protected areas, they do so without a vital piece of the puzzle.